The Concept of Syed Muhammad Naquib al-Attas on De-Westernization and its Relevancy toward Islamization of Knowledge - Nabila Huringiin; Halimah Nisrina Azfathir (Universitas Darussalam Gontor, 2018)
This article tries to discuss the concept of de-westernization of Syed Muhammad Naquib al-Attas and its relevancy toward Islamization of knowledge. De-Westernization is an effort which necessity to do to win the challenge in the knowledge field that caused by Western civilization nowadays. In brief, de-westernization is an identification, separation, and isolation process from the elements of Western in the body of knowledge. This process stood as the first step to treat the dilemma which is resulted by skepticism and relativism with Islamization of knowledge. However, Islamization of knowledge should be doing after investing the Islamic worldview and Islamization of language. Also should be identifying the elements of westernization before doing the de-westernization. Naquib al-Attas stated that the language is a reflection of the worldview of someone or some civilization. Moreover, language is put into the category of Islam according to its vocabulary. It should relate to vocabulary in Islam. The concept of de-westernization as a first step before going to Islamization of knowledge begins by setting Islamic worldview before because it has a big impact on the way of think. Thus, the writer tries to declare the concept of Syed Muhammad Naquib al-Attas and its relevancy toward Islamization of knowledge.